Analisis Skandal Koperasi Indosurya dan Kegagalan Pengelolaannya - Putri, Alitha Sulistyo; Kirani, Marsyah; Hidayati, Azizah Rizqina; Sadi, Multias Febriana (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This paper provides an in-depth analysis of the Indosurya Savings and Loan Cooperative (KSP) scandal, one of the most notable cases in Indonesia’s cooperative history. A cooperative, which is fundamentally based on principles of mutual cooperation and family values, became entangled in issues of non-transparent fund management, suspected Ponzi schemes, weak regulatory oversight, and high-risk investments. The scandal led to significant financial losses, amounting to trillions of rupiah, and severely eroded public trust in cooperatives as business entities. Legally, the lack of robust regulations and inadequate supervision of large cooperatives were identified as key problems. This study examines the background, principles, types, and legal foundations of cooperatives, while also analyzing the impacts and resolutions of this case. Findings highlight the urgent need for regulatory reform, enhanced education and awareness among members, and stronger oversight by regulators to prevent similar incidents in the future.